Valuing Corporate Brands - Gregory, James R. (Henry Stewart Talks, 2014)
Complexity of valuing brands, Corporate brand as an intangible asset, Why brand valuation matters, Building tangible accountability for intangible assets, Identifying the brand's direct impact on market cap, Aflac: a case study in brand equity, Isolating brand impact from market noise, Putting your brand in context